Determinants of dividend policy: A case of Serbia's banking sector - Biljana Jovković; Aleksandra S. Vasić; Jasmina Bogićević (Naše gospodarstvo / Our Economy, 2021)
Dividend policy is one of the most controversial areas of corporate finance. The paper presents the results of the research in the banking sector of the Republic of Serbia. The specific characteristics of the financial sector make the research on dividend policy determinants additionally complex. This study aims to determine the factors of dividend policy in the Serbian banking sector in the period 2009-2018. The model of random effects was chosen to test the relationship between dividend determinants and dividend payout. Empirical results show that previous years' dividends have a significant positive effect on dividend policy. Individual investors can benefit from the research to a great extent, as well as bank managers, when creating dividend policies that would contribute to maximising profit and satisfying the needs of employees and shareholders in the long run.
Keywords: G21; G30; 330